2019
DOI: 10.1016/j.neubiorev.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Sugar rush or sugar crash? A meta-analysis of carbohydrate effects on mood

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 136 publications
(191 reference statements)
2
37
0
5
Order By: Relevance
“…Although previous review studies have reported that the ingestion of CHO in prolonged exercise can enhance athletes' performance and maintain their endurance [6], this study found CHO to have a significant negative effect on mental fatigue. This is in line with a previous meta-analysis that concluded that CHO ingestion does not have a beneficial effect on mood and may increase fatigue within 30 min post-consumption [46]. In reference to the mentioned results, MBI seems to have the effect of buffering the negative influence of CHO.…”
Section: Discussionsupporting
confidence: 92%
“…Although previous review studies have reported that the ingestion of CHO in prolonged exercise can enhance athletes' performance and maintain their endurance [6], this study found CHO to have a significant negative effect on mental fatigue. This is in line with a previous meta-analysis that concluded that CHO ingestion does not have a beneficial effect on mood and may increase fatigue within 30 min post-consumption [46]. In reference to the mentioned results, MBI seems to have the effect of buffering the negative influence of CHO.…”
Section: Discussionsupporting
confidence: 92%
“…However, the association with sugar-sweetened beverages is less clear. [11][12][13] When consumed in high quantities, 14 sugarsweetened beverages are associated with high glycemic load, 15,16 increased inflammation, and oxidative stress, 17 which in turn can be associated with elevated depressive symptoms. 18 Regarding prospective studies, while Guo et al 12 found that sugar-sweetened beverages were associated with higher odds of depression, Sanchez-Villegas et al 11 and Knü ppel et al 13 found inconclusive evidence of an association between sugar-sweetened beverages and depression.…”
Section: Introductionmentioning
confidence: 99%
“…They act as an energy source, help control blood glucose and insulin metabolism, and participate in cholesterol and triglyceride metabolism. An increase or decrease in carbohydrates beyond appropriate amounts can affect both physiological and metabolic processes (Mantantzis et al 2019).…”
Section: Introductionmentioning
confidence: 99%